Consensus Reached on Feeding Infants and Children. Issue 1 (January 2021) - Beal, Judy A.
Abstract : New consensus guidelines on infant feeding have been released from the National Academies of Sciences, Engineering, and Medicine. Our pediatric nursing expert, Dr. Beal, summarizes the document and offers suggestions for dissemination.